INVENTARISASI DAN IDENTIFIKASI TUMBUHAN OBAT SUB ETNIS KUTAI DESA GENTING TANAH KECAMATAN KEMBANG JANGGUT KABUPATEN KUTAI KARTANEGARA KALIMANTAN TIMUR - Anita Apriliana; Medi Hendra; Atila Sapitri (Jurnal Ilmiah Manuntung, 2016)
Indonesia has rich tropical forests will be diverse plants that can be used as a traditional medicine, ranging from roots, stems, leaves, until all fruit is of great value and can be used as a medicine for the health as well as from different tribe who were in Indonesia. Since old time sub etnic Kutai using different types of plants as a medicine because the lack of medical personnel and health care center in curing diseases. This study aims to find out the types of medicinal herbs used by tribes. The results there were 39 Medicinal plants used by tribes that is Serai, Sirih, Tumbuh daging, Kepius, Patah tulang, Kunyit root, Senuru , Mali wood, Prepat wood, lupun root, Kecubung, Terung pipit, Gelinggang, Beribit grass, Syurga leaf, Tapis bongol, Nyiur ongo, Singgah bini wood, Penggel habeng, Serkemudi grass, Tunjuk langit root, Kemet hitam, Pacar beleng, penggel putih, Ketotol grass, Kemantrah, Sahung wood, Tajerebo, Cula adem, Risip leaf, Lalang, Sampai root, Cancut haji jewa, Mersesat leaf, Lekop leaf, Kuku tupai, Kempis root, Kemet putih and Kedeme